The Effectiveness of Using Whatsapp Group to Improve Grammar Ability in Report Text of the Tenth Grade Students at SMA N 1 Prambanan in the Academic Year of 2019/2020 - Ratri Nur Hidayati; Andhika Nur Machmuda (Journal of English Language Teaching and English Linguistics, 2022)
This research discusses whether there was any significant difference or not in the improvement of students' grammar ability achievement in report text between students who were taught by using WhatsApp group and those who were not taught by using it. The population of the study was all of the tenth graders of SMA N 1 Prambanan in the academic year of 2019/2020. While the samples were the students of the X IPS 1 class as the experimental group and the students of the X IPS 2 class as the control group. Data collecting techniques used by the researcher were try-out, pre-test, and post-test. Whereas grammar tests and questionnaires were used as the research instruments. In analysing the data, it was applied descriptive analysis and inferential analysis. The results showed that the mean increase in the experimental class was higher than that in the control class. Moreover, the independent sample t-test result revealed that the value of Sig. (2-tailed) was smaller than 0,05. Therefore, the WhatsApp group was effective to be used as a media to teach grammar in report text to the tenth-grade students of SMA N 1 Prambanan in the academic year of 2019/2020.